"Effet Wow" cantilever structure at Bridge, Orange's headquarters. Issue 4 (15th October 2020) - de Sousa da Costa Lopes, Adriano Alves; Simões Breda, Ricardo André; da Silva Gonçalves, Sílvio Daniel
Abstract: Nominated for the Professor Eduardo de Arantes e Oliveira Award at XII Conference on Steel and Composite Construction in Coimbra 2019 Orange's new headquarters, Bridge, is under construction in suburban Paris. This is a project designed to centralize the company's services and its 3000 employees, who are currently scattered throughout the city. The architectural concept is unique and comprise complex forms that are highly dependent on the structural design. The building is mostly precast concrete, with several steel structures used to support the most structurally challenging areas. One of these is a two‐level roof cantilever. This article examines some of the technical challenges faced by the project team as well as the peculiarities inherent in this composite steel structure.